Delilah A.

asked • 06/02/20

Find the solution to the general exponential equation p(q)^rx=s, in terms of the constants p,r,s, and the logarithm of base q. In other words, solve for x.

Adama S.

Take log base q of both sides: log_q(p(q)^rx)=log_q(s) log_q(p)+rxlog_q(q)=log_q(s) log_q(p)+rx * 1 =log_q(s) rx= log_q(s)-log_q(p) rx= log_q(s/p) x=(log_q(s/p))/r


1 Expert Answer


Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.


Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.